Cognitive radio for TVWS usage - Diego Pineda; Cesar Hernandez (Universitas Ahmad Dahlan, 2019)
Spectrum scarcity is an emerging issue in wireless communication systems due to the increasing demand of broadband services like mobile communications, wireless internet access, IoT applications, among others. The migration of analog TV to digital systems (a.k.a. digital TV switchover) has led to the release of a significant spectrum share that can be used to support said additional services. Likewise, TV white spaces emerge as spectral opportunities that can also be explored. Hence, cognitive radio (CR) presents itself as a feasible approach to efficiently use resources and exploit gaps within the spectrum. The goal of this paper is to unveil the state of the art revolving around the usage of TV white spaces, including some of the most important methods developed to exploit such spaces, upcoming opportunities, challenges for future research projects, and suggestions to improve current models.